PROGRAM PAKAR UNTUK DEFISIENSI KELAPA SAWIT - Dian Pratama Putra Putra (AGROISTA : Jurnal Agroteknologi, 2019)
Computers have become “arteries” in our lives. All fields both directly and indirectly are always related to computers and in the current era of globalization, computers are no longer an foreign thing for us but are an indispensable need in everyday life. ECatalog is one of the information systems which can provide consistent information because in addition to getting information also provides a expertise system because from the basic idea is to transfer a expertise from someone to be implemented in a program. Deficiency is an appearance characterized by plants due to lack of nutrients. In addition to knowing the lack of nutrients, the most fatal can also cause death by plants that experience it. E-Palm oil deficiency catalog makes it easy for users to find symptoms or abnormalities in oil palm plants so that it is easy to make decisions. Keyword : oil palm, precision, nutrition